Analysis of the Effect of Compensatory Justice and Compensation Procedural Fairness on Affective Commitment and Motivation as Mediators - Amin, Muhammad; Tjahjono, Heru Kurnianto (International Conference On Economics Business Management And Accounting (ICOEMA), 2022)
This study aims to examine the effect of "The Effect Of Compensation Justice And Compensation Procedural Justice On Affective Commitment And Motivation As Mediators" (Case Study In The Company PT Hujan Hijau Mas In Berau Regency). The respondents in this study were 169 employees who worked in PT. Hutan Hijau Mas in 2017.The analysis technique used is Structural Equation Modeling with the help of the AMOS program version 21.0 as an analytical tool. This study yielded the following conclusions: 1) Compensation Distributive Justice and Compensation Procedural Justice in influence motivation 2) Motivation influences Affective Commitment, 3). Compensation Distributive Justice and Compensation Procedural Justice have an influence on Affective Commitment through Motivation.